VISUAL CULTURE OF IBAN PUA KUMBU - Noria anak, Tugang; Louis Ringah, Kanyan; Alexander, Chelum; Mawar Suhaila, Ab Razak (UNIMAS Publisher, 2024)
Pua Kumbu, also known as Pua Kebat, holds a special place in the life of the iban people. In the past, it was of immense importance in Iban culture, so much so that there was a widely accepted saying that an Iban family without a Pua Kumbu would be considered disconnected from their cultural roots. The Iban people followed heritage beliefs that placed a strong emphasis on rituals, many of which required the use of Pua Kumbu in significant quantities. While originally used as blankets, Pua Kumbu evolved into sacred objects used during Gawai rituals. They were even employed to greet the severed heads of enemies taken by Iban warriors. The motifs on Pua Kumbu were regarded as sacred, possessing mystical and extraordinary powers to protect weavers, their families, and homes from the threat of evil spirits. In the exhibited piece, the artists have incorporated large motifs, including human and animal images, as well as representations of flora and fauna